Genetic studies on familial genetic generalized epilepsy: A whole exome sequencing approach / Chan Chung Kin - Chan, Chung Kin (2021)
Genetic generalized epilepsy (GGE) is a form of epilepsy that is potentially caused by genetic factors. It accounts for 15-20% of all epilepsy worldwide and 18.7% of the epilepsy cases in Malaysia. Unlike focal epilepsy, patients with generalized epilepsy mainly rely on antiepileptic drugs to achieve seizure control. As a result, understanding of the molecular pathway behind generalized epilepsy would be beneficial as it can aid the treatment decision and the design of newer antiepileptic drugs. The pathway analyses in GGE were conducted on European population and these results may not be applied to Malaysian or Asian due to genetic variation. Hence, this project was conducted to identify the genetic factors and plausible biological processes associated with GGE in Malaysia. The project started with whole exome sequencing on 12 unrelated Malaysian probands (4 Malays, 3 Chinese and 5 Indians) and 2 unrelated Malaysian Chinese proband-parent trios, all the 14 probands were diagnosed with GGE and having family history of epilepsy. The exome sequencing data was then analysed with GATK and the variants were annotated with wANNOVAR. Following variant filtration, a 3-step functional characterization analysis encompassing gene prioritization, protein-protein interaction analysis and DAVID enrichment was conducted. The analysis found the GO terms related with sodium and calcium ion transport, such as GO:0035725, GO:0006814, GO:0070588 and GO:0070509, were highly associated with GGE among Malaysians. The active role of ion channels in epilepsy makes them an ideal therapeutic target for antiepileptic drugs in seizure suppression. From this prospective, the protein-protein interaction analysis has suggested the potential of dystrophin (DMD) to be used as therapeutic target due to its regulatory role on sodium transporters and calcium ion channels. Besides, the functional characterization analysis has also intimated the potential risk of tyrosine kinases NTRK1, NTRK2 and ERBB4 in the pathogenesis of GGE. Additionally, segregation analysis was conducted on 2 families to study the pathogenicity of the SCN1A c.5753C>T and ERBB4 c.1972A>T variants identified from this cohort. The results showed that the SCN1A variant was likely pathogenic but the ERBB4 variant was expected to induce epilepsy via an interaction with gamma-aminobutyric acid type A (GABA-A) receptor gene GABRA1 c.448G>A variant. A disease model illustrating the combined effect between the mutant ERBB4 and GABRA1 in GGE pathogenesis was proposed, this hypothesized disease model may provide a new insight on the impact of ERBB4 in the disturbance of inhibitory postsynaptic current (iPSC) and excitation-inhibition (E/I) balance. While this project is just a preliminary study on the genetics behind GGE among Malaysians, this study has demonstrated that ion channels are not the only cause of GGE, tyrosine kinases may also contribute to GGE by manipulating numerous biological pathways like the expression of GABA-A receptors. Moreover, the identification of DMD as a potential therapeutic target warrants further investigation as the findings may contribute to the design of new antiepileptic drugs in future.